The Impact of Age on Mortality in Patients in Extremis Undergoing Urgent Intervention. Issue 12 (December 2013) - McClellan, Eric B.; Bricker, Scott; Neville, Angela; Bongard, Frederic; Putnam, Brant; Plurad, David S.
Trauma patients admitted without vital signs have little hope of survival even with extreme interventions. We performed this study to determine the effect of age on survival in patients in extremis undergoing urgent thoracotomy. The National Trauma Database was searched for patients presenting without a systolic blood pressure (0), a Glasgow Coma Scale score less than 8, and underwent an urgent thoracotomy. Mortality was determined for pediatric (younger than 16 years) and older patients (older than 60 years) and compared. Of 708 patients, 32 (4.5%) were pediatric and 57 (8.1%) were elderly. Pediatric mortality was 93.8 per cent (30) versus 95.6 per cent (646) for patients older than 16 years ( P = 0.981). Mortality in the older patients was 94.7 per cent (54) versus 95.5 per cent (622) in patients younger than 60 years ( P = 0.778). Race and blunt injury were independently associated with death. However, neither pediatric ( P = 0.418) nor older status ( P = 0.184) was predictive. Age does not significantly impact mortality in patients in extremis who undergo urgent thoracotomy. Age should not be a contributing factor in determining who should undergo more extreme maneuvers if they present as a reasonable candidate using other criteria.